Design, Synthesis and Pharmacological Evaluation of a Series of 5-Carbethoxy-4-chloro-6-(substituted amino)pyrimidines as Potential Analgesic and Anti-flammatory Agents with Very Low Ulcerogenic Potential - Mahesh, T Chhabria; Chamanlal, J Shishoo; Dilip, K Vaghela; Shailesh, M Patel; Milan, C Satia (Arzneimittelforschung, 2009)
A series of 5-carbethoxy-4-chloro-6-(substituted amino)pyrimidines was designed on the basis of its good 3-dimensional structural similarity with mefenamic acid (CAS 61-68-7), a well known anti-inflammatory drug. Synthesis of some 5-carbethoxy-4-chloro-6-(substitutedamino) pyrimidines has been achieved by cyclization of N-(cyanovinyl)formamidine intermediate in the presence ofdry HCl. Target compounds were evaluated for their analgesic and anti-inflammatory potential by known experimental models. Some of the compounds emerged as more potent analgesic and anti-inflammatory agents than the standard drug diclofenac sodium (CAS 15307-79-6). A very low ulcer index was observed with the most potent compound.
Keywords: 4-Chloropyrimidine, analgesic activity, anti-inflammatory activity, ulcerogenic potential; N-(Cyanovinyl)formamidine